Pengaruh Latihan Pernapasan Diafragma Terhadap Arus Puncak Ekspirasi Pada Anak Yang Mempunyai Hobi Renang Usia 9 - 15 Tahun - Widyawati, Fiqi; , Dwi Kurniawati SSt.Ft, M.Kes (2016)
Background: The lungs are one of the most important organ in the human body. Vital lung capacity is a most important measure for assessing lung function, which may increase or decrease. Improve lung function can be done by train and one of them is by swim. Objective: know the effect of diaphragmatic breathing exercises to peak expiratory flow in children who have a hobby of swimming age 9-15 years old. Methods: The research used quasi experiment method to approach pre test and post test one group design. Research subjects were 27 children were selected by Random Sampling divided into 2 group, 14 children in treatment group and 13 children as a control group. Data analysis using the wilcoxon test the effect on different test while using the influence mann-whitney test. Result: the effect between treatment group by diaphragmatic breathing exercises with a control group who were not given diaphragmatic breathing exercises, the results (p=0,225), so nothing a significant relationship between the two variables. Conclusions: nothing the effect of diaphragmatic breathing exercises to peak expiratory flow in children who have a hobby of swimming age 9-15 years old.